IDENTIFIKASI ASPEK HUKUM PENERAPAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) PADA SEKTOR PARIWISATA BALI (STUDI KASUS DI KABUPATEN BADUNG BALI) - I Putu Agus Suarsana Ariesta (Universitas Triatma Mulya, 2021)
The Covid-19 pandemic is a typical issue that has made nations on the planet experience fearful conditions, including the financial and the travel industry areas being incapacitated. Companies are affected, especially because many workers cannot work due to being laid off, making it difficult to meet the daily needs of their families. Indonesia is one of the nations influenced by the Covid-19 pandemic, as proven by the decrease in state pay since it makes numerous guidelines for current crisis spending to help the endurance of its residents which is a type of the focal government's anxiety for its residents. The attention of the Indonesian government in fighting Covid-19 includes facilitating its citizens to receive vaccines, then regulating and implementing regulations that support economic and health recovery with health protocols and distributing social assistance to affected citizens to survive. The implementation of an emergency Community Activity Restriction (Pemberlakuan Pembatasan Kegiatan Masyarakat / PPKM) which has been declared by the central government in an effort to overcome the Covid-19 outbreak and if it is deemed necessary, a regular and directed extension of the PPKM will be applied according to the levels given by the government.